Instrument to Assess the Farmers’ Participation in Effective Canal Irrigation Management - Naik, Akkamahadevi; Shivamurthy, M; Chandre Gowda, MJ (Indian Journal of Extension Education, 2021)
The method of summated rating scale suggested by Likert (1932) and Edwards (1969) were followed to develop an instrument through six stages ; identification of dimension, collection of items/statements, relevancy analysis, item analysis, reliability and validity of the scale. Six dimensions viz., farmers’ participation in the formulation of guidelines, planning and implementation activities, maintenance activities, responsibility sharing, crop planning activities, and integrated crop management were listed and 60 items/statements were enlisted. Based on the relevancy percentage equal and more than 80.00 percent and the mean relevancy score of equal and more than 4.00 were considered for inclusion in the item analysis. After the relevancy analysis and item analysis, out of 60 items/statements, 34 statements were retained. The scale values for each of the identified dimensions by adopting normalized ranking method recommended by Guilford (1954) and the total scale value ranges from 9.340 to 2.537, with farmers’ participation in integrated crop management got the highest rank and formulation of guidelines got the lowest rank. The developed instrument was found to be reliable (0.96) and valid (0.98), hence it can be used to measure farmers’ participation in effective canal irrigation management.